Traditional Self-Governing Institution of the Co Ho Sre People in Lam Dong in Current Social Life - Tu, Vo Tan; Bong, Phan Van (Journal of Ecohumanism, 2024)
The Co Ho Sre people, the largest local group within the Co Ho ethnic group, had a long-standing culture, highlighted by developed wet rice farming and stable settlements in their villages. The village of the Co Ho served as a traditional social organization with essential functions in organizing, managing, and operating the community regarding economy, society, culture, and ethnic consciousness in a context of low development. The traditional self-governing institution of the Co Ho village relied on customary laws and the prestige of the village chief to govern all activities within the village. Although there have been many changes in social management, the self-governing institution of the Co Ho Sre still retained many positive elements, playing an essential role in building the Co Ho Sre community in particular and minority ethnic communities in Lam Dong in general. The article applied synthesis and analysis methods along with survey and interview methods to reconstruct the traditional self-governing institution and evaluate its role in the current life of this ethnic group.